Cadeia global de valor de eletrônicos e inserç\~ao do vietn\~a e da Malásia - Eduardo Costa Pinto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper aims at: i) presenting the evolution and features of the Global Value Chain electronics in the 2000s; and ii) analyzing the general lines of the Vietnam and Malaysia insertion in Global Value Chains (CVG) electronics, seeking to identify the exogenous and endogenous determinants of this process and differences in the current stages of integration of these countries.
Keywords: F15; F63; L22; L23; L52; 330; economic integration; economic development; value chains